Pharmacological activation of soluble guanylate cyclase improves vascular graft function - Veres, Gábor; Bai, Yang; Stark, Klára Aliz; Schmidt, Harald; Radovits, Tamás; Loganathan, Sivakkanan; Korkmaz-İçöz, Sevil; Szabó, Gábor (Interactive cardiovascular and thoracic surgery, 2021)
Ischaemia-reperfusion injury impairs the nitric oxide/soluble guanylate cyclase/cyclic guanosine monophosphate (cGMP) signalling pathway and leads to vascular dysfunction. We assessed the hypothesis that the soluble guanylate cyclase activator cinaciguat would protect the vascular graft against ischaemia-reperfusion injury.In the treatment groups, rats (n = 8/group) were pretreated with either intravenous saline or intravenous cinaciguat (10 mg/kg) 2 h before an aortic transplant. Aortic grafts were stored for 2 h in saline and transplanted into the abdominal aorta of the recipients. Two hours after the transplant, the grafts were harvested and mounted in an organ bath. Vascular function of the grafts was investigated in the organ bath. Terminal deoxynucleotidyl transferase dUTP nick end labelling, cluster of differentiation 31, caspase-3, endothelial nitric oxide synthase, cGMP, nitrotyrosine and vascular cell adhesion molecule 1 immunochemical reactions were also investigated.Pretreatment with cinaciguat significantly improved endothelium-dependent maximal relaxation 2 h after reperfusion compared with the saline group (maximal relaxation control: 96.5 ± 1%, saline: 40.4 ± 3% vs cinaciguat: 54.7 ± 2%; P < 0.05). Pretreatment with cinaciguat significantly reduced DNA fragmentation and nitro-oxidative stress; decreased the caspase-3 and vascular cell adhesion molecule 1 scores; and increased endothelial nitric oxide synthase, cGMP and cluster of differentiation 31 scores.Our results demonstrated that enhancement of cGMP signalling by pharmacological activation of the soluble guanylate cyclase activator cinaciguat might represent a beneficial therapy for treating endothelial dysfunction of arterial bypass graft during cardiac surgery.